The Role of Emotions, Moral Disengagement and Gender in Supporting Victims of Bullying - Maria Carmen Cabrera; Elisa Larrañaga; Santiago Yubero (MDPI AG, 2020)
Previous research shows that classmates supporting victims' defence is fundamental to combat bullying. To find a suitable response for the bullying problem, we must bear in mind how all the victim's classmates respond and what variables can determine their helping behaviour. Moral disengagement has been demonstrated to be a factor that explains behaviour when faced with bullying. Emotions have also been shown to be relevant for bullying behaviour. This research aimed to gain knowledge of how adolescents behave when faced with bullying and to analyse how their behaviour relates to moral disengagement and both positive and negative emotions, specifically supportive behaviour for victims. In the present study 1029 students participated, all of whom came from Secondary Education, Training Cycles and Higher Secondary Education Stages in Spain. The regression analysis confirmed that being male increased the likelihood of performing active and passive behaviours. Conversely, being female involved displaying more proactive behaviours. Feeling positive/pleasant emotions about bullying increased active behaviour. Feeling negative/unpleasant emotions about bullying increased behaviour in the proactive behavior group. Adolescents should be aware that stopping bullying is their personal responsibility, which depends on their behaviour with the victim. Interventions must aim to reduce moral disengagement and positive emotions about bullying by increasing negative emotions about such behaviour.